PRELIMINARY STUDY OF THE JUVENILE FISHES OF THE COASTAL WATERS OFF MADRAS CITY - Basheeruddin, S; Nayar, K Nagappan (Indian Journal of Fisheries, 2011)
IT has generally been observed that in the commercial catches along theMadras coast very young stages of fish occur in enormous numbers duringcertain months. The present paper deals with the periodicity in the postlarvaland juvenile bony fishes obtained from March 1954 to July 1955collected from the fishing centres at Triphcane North and South, Ayodhyakuppam,Nochikuppam, Santhome, Kanniappanagar and Royapuram. Themajority of the species being of great commercial importance, it is hopedthat a record of their very young stages, apparently not older than a fewmonths, as judged by their very small size of about few cm. in length, willhelp in fixing the approximate period of their breeding and in facilitatinginterpretation of the different size classes, usually obtained in the commercialcatches. Further, it is well known that information on the fluctuations inthe abundance of post-larvae of any commercial fish is of value in determiningthe magnitude of the forthcoming fisheries.